Peningkatan Literasi Sekolah Guru dan Siswa melalui Pengabdian Kepada Masyarakat Perpustakaan STIE Perbanas Surabaya - Melati Purba Bestari; M. Hudhan Hakiki (Institut Agama Islam Negeri Salatiga, 2018)
The phenomenon of information explosion supported by the development of informationtechnology to overcome the required information literasi kemapuan. The ability of informationliteracy to support the activities of searching, evaluating, and using informationappropriately. Information literacy should be owned by the academic community notexcluded the school community for teachers and students. The existence of PermendikbudNo.23 of 2015 requires schools to carry out activities “School Literacy Movement includesbasic literacy, library, media technology and libraries, and sharing opportunities withrepresentatives of teachers in Counseling Teacher Consultative Forum (MGBK) SurabayaLibrary STIE Perbanas Surabaya held community service activities related to schoolliteracy improvement. The target schools include SMAN 15 Surabaya and SMA WachidHasyim 1. Literacy improvement activities include sharing information literacy activitieswith teachers, librarian lectures and competence activities of short story competitions.The results of the service activities include the establishment of cooperation related to thedevelopment of school literacy contained in the MoU, students’ understanding of schoolliteracy which reached 63% and the publication of a collection of short stories ISBN.